Tinea capitis due to Trichophyton soudanense and Microsporum audouinii: A surprising finding - Frederik Krefting; Elisabeth Livingstone; Wiebke Sondermann; Carl M. Thielmann; Jan‐Malte Placke; Dirk Schadendorf; Christina Polan; Peter Michael Rath; Ulrike Scharmann; Silke Uhrlaß; Pietro Nenoff (Wiley, 2024)
Abstract Tinea capitis is a prevalent dermatophyte infection among German children, primarily caused by Microsporum canis, Trichophyton mentagrophytes and Trichophyton benhamiae. Other pathogens, such as T. soudanense and M. audouinii, have also been identified in Germany. This case report describes a 10‐year‐old Angolan girl with chronic osteomyelitis who was brought to Germany for treatment, which was organized by the Friedensdorf International (Peacevillage International). In addition to chronic osteomyelitis of the lower leg, the patient presented with alopecic areas of the scalp with adherent scales, which raised the suspicion of tinea capitis. Fungal cultivation and polymerase chain reaction (PCR) diagnostics revealed a coinfection of T. soudanense and M. audouinii, which, to the best of our knowledge, has not been previously reported in Europe. After 4 weeks of systemic terbinafine treatment and topical use of ciclopirox solution and clotrimazole cream, there was a marked improvement in the patient's condition. This was confirmed by a negative fungal culture and PCR; no adverse events were reported. This report highlights a rare dual dermatophyte infection caused by T. soudanense and M. audouinii in Europe, and the successful response to treatment with systemic terbinafine and topical ciclopirox solution as well as clotrimazole cream.